Beispiel Nr: 07
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ -2 x +2 + 4 z=0\\ 4 x -\frac{1}{2} y + 2 z=5\\ 4 x -2 y + -1 z=8\\ \\ \\ \textbf{Rechnung:} \\ -2 x + 2 y + 4 z=0\\ 4 x -\frac{1}{2} y +2 z=5\\ 4 x -2 y -1 z=8\\ D_h=\left|\begin{array}{ccc} -2\ & 2 & 4\\ 4&-\frac{1}{2} & 2\\ 4& -2 & -1 \\ \end{array}\right| \begin{array}{cc} -2\ & 2 \\ 4&-\frac{1}{2} \\ 4& -2 \end{array} \\ D_h=\left(-2\right) \cdot \left(-\frac{1}{2}\right) \cdot \left(-1\right)+2 \cdot 2 \cdot 4 +4 \cdot 4 \cdot \left(-2\right) - 4 \cdot \left(-\frac{1}{2}\right) \cdot 4 -\left(-2\right) \cdot 2 \cdot \left(-2\right) -2 \cdot 4 \cdot \left(-1\right)=-9 \\ D_x=\left|\begin{array}{ccc} 0\ & 2 & 4\\ 5&-\frac{1}{2} & 2\\ 8& -2 & -1 \\ \end{array}\right| \begin{array}{cc} 0\ & 2 \\ 5&-\frac{1}{2} \\ 8& -2 \end{array} \\ D_x=0 \cdot \left(-\frac{1}{2}\right) \cdot \left(-1\right)+ 2 \cdot 2 \cdot 8 +4 \cdot 5 \cdot \left(-2\right) - 4 \cdot \left(-\frac{1}{2}\right) \cdot 8 - 0 \cdot 2 \cdot \left(-2\right) -2 \cdot 5 \cdot \left(-1\right)=18\\ D_y=\left|\begin{array}{ccc} -2\ & 0 & 4\\ 4&5 & 2\\ 4& 8 & -1 \\ \end{array}\right| \begin{array}{cc} -2\ & 0 \\ 4&5 \\ 4& 8 \end{array} \\ D_y=\left(-2\right) \cdot 5 \cdot \left(-1\right)+0 \cdot 2 \cdot 4 +4 \cdot 4 \cdot 8 - 4 \cdot 5 \cdot 4 -\left(-2\right) \cdot 2 \cdot 8 -0 \cdot 4 \cdot \left(-1\right)=90 \\ D_z=\left|\begin{array}{ccc} -2\ & 2 & 0\\ 4&-\frac{1}{2} & 5\\ 4& -2 & 8 \\ \end{array}\right| \begin{array}{cc} -2\ & 2 \\ 4&-\frac{1}{2} \\ 4& -2 \end{array} \\ D_z=\left(-2\right) \cdot \left(-\frac{1}{2}\right) \cdot 8+2 \cdot 5 \cdot 4 +0 \cdot 4 \cdot \left(-2\right) - 0 \cdot \left(-\frac{1}{2}\right) \cdot 4 -\left(-2\right) \cdot 5 \cdot \left(-2\right) -2 \cdot 4 \cdot 8=-36\\ x=\frac{18}{-9} \\ x=-2 \\ y=\frac{90}{-9} \\ y=-10 \\ z=\frac{-36}{-9} \\ z=4\\ L=\{-2/-10/4\} $